Quiroga, Hugo; Villavicencio, Susana; Vermeren, Patrice (comp.). Filosofías de la ciudadanía. Sujeto político y democracia. Rosario (Argentina), Homo Sapiens Ediciones, 1999, 260p. - Muñoz, Marisa Alejandra (1999)
Fil: Muñoz, Marisa Alejandra.